2006
DOI: 10.1071/ar04275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of available nutrition and sire breeding values for growth and muscling on the development of crossbred lambs. 1: Growth and carcass characteristics

Abstract: Abstract. The growth and development of 387 crossbred lamb progeny from 9 Poll Dorset sires representing muscle (M), control (C), and growth (G) sire-types was studied. Sires were selected on the basis of their LAMBPLAN estimated breeding values (EBVs) for post-weaning growth (PWWT) and depth of loin muscle (PEMD). Lambs were provided with either LOW or HIGH levels of available grazing nutrition from 10 days of age onwards. Liveweight gain (LWG) throughout the study was less on LOW nutrition than on HIGH nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 19 publications
3
14
1
2
Order By: Relevance
“…This contradicts previous findings from smaller studies where PWWT had no effect , though it does support the general principle that lambs selected for high post weaning weights would have a larger mature size (Huisman & Brown, 2008) and therefore they will be physiologically less mature when compared at the same weight (Berg & Butterfield, 1968;Butterfield et al, 1983;Hegarty, Shands, et al, 2006) …”
Section: Pwwt Asbvcontrasting
confidence: 96%
See 1 more Smart Citation
“…This contradicts previous findings from smaller studies where PWWT had no effect , though it does support the general principle that lambs selected for high post weaning weights would have a larger mature size (Huisman & Brown, 2008) and therefore they will be physiologically less mature when compared at the same weight (Berg & Butterfield, 1968;Butterfield et al, 1983;Hegarty, Shands, et al, 2006) …”
Section: Pwwt Asbvcontrasting
confidence: 96%
“…This appears to align with suggestions made in previous studies, where selection for increased PEMD resulted in an increase in loin depth and weight Hegarty, Shands, et al, 2006;Hopkins, Stanley, Martin, Ponnampalam, et al, 2007), and little effect elsewhere in the carcass. Alternatively, these previous experiments were unable to clearly demonstrate redistribution of lean to the saddle as fore section lean was not recorded and only a small number of indicator muscles (e.g.…”
Section: Pemd Asbvsupporting
confidence: 90%
“…Hegarty et al (2006a and found that the selection of sires with increasing eye muscle depth ASBV resulted in lamb carcases with reduced C-site fat depth, less intramuscular fat within the loin muscle and less total carcase fat, a similar trend to that observed by Hocquette et al (1999) in double-muscled Belgian Blue cattle. In times of psychological or physical stress (such as mustering, transportation or starvation), animals have the ability to mobilise their adipose tissue to form non-esterified fatty acids (NEFA), which then has to be oxidised to form energy in other tissues (Chilliard et al, 2000).…”
Section: Introductionmentioning
confidence: 52%
“…Thus, the reduced glucose output due to selection for muscling may be linked to any one or a combination of these glucose sources; however, reduced liver gluconeogenesis as a result of lower circulating growth hormone is a possible cause of this effect. Progeny from high muscling sires have shown reduced growth rates to weaning, reduced bone growth and increased muscle-to-bone ratio (Cake et al, 2006;Hegarty et al, 2006a), all suggestive of reduced growth hormone. Furthermore, studies using growth hormone transgenic sheep reported a decrease in eye muscle depth due to increased growth hormone (Adams et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the concept of fat scoring live lambs to predict GR tissue depth was developed and used with liveweight to market young sheep for meat (Kirton et al 1991;Hegarty et al 2006). Initially, fat score assessors 'felt lambs by hand mainly over the backbone and tail stump' (Kirton et al 1991) and were as accurate as ultrasonic machines, which measure fat over the eye muscle (Bass et al 1982; as cited in Kirton et al 1991).…”
Section: Introductionmentioning
confidence: 99%